5(x+3)+3=5x+1

Simple and best practice solution for 5(x+3)+3=5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+3=5x+1 equation:


Simplifying
5(x + 3) + 3 = 5x + 1

Reorder the terms:
5(3 + x) + 3 = 5x + 1
(3 * 5 + x * 5) + 3 = 5x + 1
(15 + 5x) + 3 = 5x + 1

Reorder the terms:
15 + 3 + 5x = 5x + 1

Combine like terms: 15 + 3 = 18
18 + 5x = 5x + 1

Reorder the terms:
18 + 5x = 1 + 5x

Add '-5x' to each side of the equation.
18 + 5x + -5x = 1 + 5x + -5x

Combine like terms: 5x + -5x = 0
18 + 0 = 1 + 5x + -5x
18 = 1 + 5x + -5x

Combine like terms: 5x + -5x = 0
18 = 1 + 0
18 = 1

Solving
18 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -1000+20t+(2.5)t^2=-30t+(1.6)t^2 | | x^2-46x+525=o | | X-10-4=2 | | -6(x-2)-7=-7x+2 | | 9(17/18x-7/27y) | | (5x+20)=70 | | 10y-46=2y+18 | | x^2-45+500=0 | | 12n-19=53 | | t+-23=-12 | | 18x-12=3-4(3x-1) | | 2x=(3x-20) | | 2500=x^(9/10) | | 2m^2-3m+16=6 | | x^2-41x+408=0 | | 3(5y+3)+5y=-6 | | 33=-y/4 | | 5(5y+3)+5y=-6 | | 7+5m=-18 | | 3w=-21 | | -10(v-8)=70 | | x^2-45x+494=0 | | -2/5m=6/11 | | -4a-4=-8 | | -6=u-3 | | 0.26x+0.18x=-3.08 | | 7+9s=10s | | 2(m-8)=-22 | | 0.10=x/0.08 | | -6z=-5z+8 | | 7X-83=33+3X | | x^2-46x+513=0 |

Equations solver categories